2015
DOI: 10.1021/acscatal.5b01354
|View full text |Cite
|
Sign up to set email alerts
|

Role of Steric Attraction and Bite-Angle Flexibility in Metal-Mediated C–H Bond Activation

Abstract: We show quantum chemically that, contrary to common believe, bulky ligands in d 10 -ML 2 complexes may enhance, instead of counteract, L−M−L bite-angle bending. The resulting more flexible or even nonlinear geometry translates into lower barriers for oxidative addition of the methane C−H bond to these complexes. This follows from our quantum chemical analyses of the bonding in and reactivity of bisphosphine palladium complexes Pd(PR 3 ) 2 with varying steric bulk, based on relativistic dispersion-corrected DFT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
60
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 124 publications
5
60
0
1
Order By: Relevance
“…for the C−F⋅⋅⋅F−C interaction, which was responsible for the integrity of a self‐assembled 2D supramolecular architecture using fully fluorinated compounds . The Δ E values of comparable magnitude have been reported for other non‐covalent interactions …”
Section: Resultssupporting
confidence: 58%
“…for the C−F⋅⋅⋅F−C interaction, which was responsible for the integrity of a self‐assembled 2D supramolecular architecture using fully fluorinated compounds . The Δ E values of comparable magnitude have been reported for other non‐covalent interactions …”
Section: Resultssupporting
confidence: 58%
“…Since the bite angle was in “opposite” relationship with the yaw distortion, it was expected that complexes 6 – 10 , which have larger bite angles, should have higher activity than complexes 1 – 5 , which have smaller bite angle; this was also evidenced from Figure d. Here also, complex 8 was found to deviate by not obeying the correlation. Recent theoretical studies showed that more flexible or non‐linear geometry translated into a lower barrier for oxidative addition of bonds to complexes of type d 10 ‐ML 2 in which L is bulky phosphine ligands . In line with this, it is worth noting that the orientation of the C NHC with respect to phenyl ring could also affect the activity of complexes, because it could alter the accessibility and the steric environment around the iridium center.…”
Section: Resultsmentioning
confidence: 87%
“…Further Valence Bond studies have revealed [78], in line with our conclusions, that, apart from the crucial dispersion term, also the σ/σ*(C-H) polarization/charge transfer and electrostatic contributions are important. Recently, numerous reports are present in the literature on the stabilizing nature of CH¨¨¨HC interactions in various types of hydrocarbons [37,38,[79][80][81][82][83][84][85], as well as their importance in catalysis [42,43,86].…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that these types of connections are intuitively considered as destabilizing due to the lack of electrostatic attraction between hydrogen atoms-homopolar dihydrogen interactions (especially the intramolecular ones) are still a matter of debate in the literature [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. Very recently more and more evidence has been reported in the literature that highlight the stabilizing nature of homopolar dihydrogen interactions [17,21,29,[36][37][38][39][40][41][42][43][44][45][46]. Accordingly, in this work we provide complementary results which shed light on energetic, quantitative and qualitative characteristics of non-covalent interactions that contribute to the stability of LiN(CH3)2BH3 and KN(CH3)2BH3 crystals.…”
Section: Introductionmentioning
confidence: 99%